Early Communist China Two Studies - Suleski, Ronald (Michigan Monographs In Chinese Studies, 2020)
Contains two detailed case studies. In "The Fu-t'ien Incident, December 1930," Ronald Suleski describes the pivotal incident in the power struggle between Mao Zedong and the Communist Central Committee. Daniel Bays's study of "Agrarian Reform in Kwangtung, 1950-1953" focuses upon the measures taken by the Chinese Communist Party to control and eventually collectivize rural elites in Kwangtung province.